Clinical Outcomes of Transferred Versus Onsite Primary Percutaneous Coronary Intervention for Patients With STEMI: Time to Look Beyond Door to Balloon Time. Issue 1 (March 2018) - Mallidi, Jaya; Visintainer, Paul; Pallekonda, Indupriya; Fisher, Daniel; Barringhaus, Kurt; Kugelmass, Aaron; Lotfi, Amir
Abstract : Background: It is currently unknown if the delay due to practical aspects associated with transfer of patients from a non-percutaneous coronary intervention (PCI) facility to a primary PCI facility is associated with adverse outcomes. Methods: We conducted a retrospective cohort study of all patients who presented with ST-segment elevation myocardial infarction (STEMI) and underwent primary PCI in 2 large regional STEMI centers in Massachusetts between January 2005 and June 2009. The cohort was divided into onsite patients who presented directly to the primary PCI center and transferred patients referred from another facility. The primary outcome was a composite of in-hospital major cardiovascular events (death, myocardial infarction, and stroke). Secondary outcomes were the individual components of the composite endpoint and bleeding complications. Results: The cohort included a total of 1236 patients. Among them, 426 (34%) patients were transferred patients and 810 (66%) were onsite patients. The median door to balloon time was significantly higher at for transferred patients (124 vs. 71 minutes). There was no significant difference in primary composite endpoint between the 2 groups (onsite 3.8% vs. transfer 5.3%, odds ratio 1.50, 95% confidence interval 0.79–2.84; P = 0.21). Adjusted risk estimates did not show a statistical difference in all-cause bleeding rates between the groups (onsite 10.1% vs. transfer 7.3%, odds ratio 0.68, 95% confidence interval 0.41–1.14; P = 0.14). Conclusions: This study confirms that well-established and integrated regional STEMI programs provide equivalent care to transferred patients and onsite patients. Parameters beyond door to balloon times should be investigated for their contributions to improve patient outcomes.